2011
DOI: 10.1007/s00128-011-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Kinetics of Trifloxystrobin and Tebuconazole on Chili and Soil

Abstract: Dissipation of trifloxystrobin and tebuconazole were studied following two applications of a combination formulation of Nativo 75 WG (trifloxystrobin 25% + tebuconazole 50%) @ 250 and 500 g ha(-1) at 10 days interval. Samples of chili were collected at 0, 1, 3, 5, 7, 10 and 15 days after the last application. Red chili and soil samples were collected after 20 days of last application. Half-life period for trifloxystrobin were found to be 1.81 and 1.58 days and for tebuconazole these values were observed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 3 publications
3
17
0
Order By: Relevance
“…Soil samples collected after 15 days did not reveal the presence of trifloxystrobin and its metabolite CGA 32113 at determination limit of 0.05 mg kg -1 . These results were in agreement with findings of earlier workers [13], who reported initial deposits of trifloxystrobin on chilli to be 0.31 and 0.59 mg kg -1 , following two applications of Nativo 75 WG @ 250 and 500 g ha -1 , and residues dissipated with half life of 1.81 and 1.58 days, respectively. Similarly, 0.30 and 0.87 mg kg -1 initial deposits of trifloxystrobin were reported on grapes at single (175 g ha -1 )and double dose (350 g ha -1 ) of Nativo 75 WG, respectively [10].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Soil samples collected after 15 days did not reveal the presence of trifloxystrobin and its metabolite CGA 32113 at determination limit of 0.05 mg kg -1 . These results were in agreement with findings of earlier workers [13], who reported initial deposits of trifloxystrobin on chilli to be 0.31 and 0.59 mg kg -1 , following two applications of Nativo 75 WG @ 250 and 500 g ha -1 , and residues dissipated with half life of 1.81 and 1.58 days, respectively. Similarly, 0.30 and 0.87 mg kg -1 initial deposits of trifloxystrobin were reported on grapes at single (175 g ha -1 )and double dose (350 g ha -1 ) of Nativo 75 WG, respectively [10].…”
Section: Resultssupporting
confidence: 93%
“…On grapes, the average initial deposit of tebuconazole were estimated to be 0.53 and 1.22 mg kg -1 , following four application of Nativo 75 WG (trifloxystrobin 250+ tebuconazole 500 g mg -1 ) at 175 and 350 g ha -1 , respectively which were in conformity with results of the present study [10]. Similarly, initial deposits of tebuconazole on chilli were found to be 0.95 and 1.88 mg kg -1 , respectively, following two application of Nativo 75WG (trifloxystrobin 25%+ tebuconazole 50%) @ 250 and 500 g ha -1 , which dissipated with half life values of 1.37 and 1.41 days, respectively [13]. However, the dissipation study of tebuconazole in peppermint revealed that three applications of tebuconazole @ 125 and 250 g a.i.…”
Section: Resultssupporting
confidence: 91%
“…Similar gradual decrease in fungicide residues after application on crop was reported earlier by Sahoo et al, (2012) in chilli and Malhat (2013) in tomato. The previous studies of various scientists were mainly focussed on the topics like pesticide residue dissipation and safe consumption intervals after pesticidal spray on vegetables, fruits and other food crops.…”
Section: Dissipation In Seedlingssupporting
confidence: 88%
“…Owing to the broad-spectrum activity and outstanding environmental tolerability, trifloxystrobin has been marketed globally for several years, and also has been widely applied to control fungal diseases in various crops such as wheat (Kaur et al, 2012), apple (Patyal et al, 2013), grape (Jyot et al, 2010), onion (Mohapatra, 2014), and typically in rice cultivation to ensure yields (Chen et al, 2014). However, profiles of residual pattern of trifloxystrobin in environment, particularly in the rice paddy ecosystem, are poorly understood (Kaur et al, 2012;Mohapatra, 2014;Sahoo et al, 2012). Furthermore, disclosure of the fate of trifloxystrobin in rice paddy ecosystem would be an appropriate indicator for understanding of its ecological risk and the side effect on human beings.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, gas chromatography (GC) (Jyot et al, 2010;Kaur et al, 2012;Mohapatra, 2014;Sahoo et al, 2012), liquid chromatography with tandem mass spectrometry (LC-MS/MS) (Chen et al, 2014), ASE-LC-MS/MS (Chen et al, 2008) and immunochemical methods (Mercader et al, 2014) have been developed to analyze trifloxystrobin in foodstuffs. Nevertheless, few methodologies were available for rapid analysis of trifloxystrobin in environmental samples (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%